Stress alters personal moral decision making - Youssef, Farid F.; Dookeeram, Karine; Basdeo, Vasant; Francis, Emmanuel; Doman, Mekaeel; Mamed, Danielle; Maloo, Stefan; Degannes, Joel; Dobo, Linda; Ditshotlo, Phatsimo; Legall, George (Psychoneuroendocrinology, 2012)
While early studies of moral decision making highlighted the role of rational, conscious executive processes involving frontal lobe activation more recent work has suggested that emotions and gut reactions have a key part to play in moral reasoning. Given that stress can activate many of the same brain regions that are important for and connected to brain centres involved in emotional processing we sought to evaluate if stress could influence moral decision making. Sixty-five undergraduate volunteers were randomly assigned to control (n=33) and experimental groups (n=32). The latter underwent the Trier Social Stress Test (TSST) and induction of stress was assessed by measurement of salivary cortisol levels. Subjects were then required to provide a response to thirty moral dilemmas via a computer interface that recorded both their decision and reaction time. Three types of dilemmas were used: non-moral, impersonal moral and personal moral. Using a binary logistic model there were no significant predicators of utilitarian response in non-moral and impersonal moral dilemmas. However the stressed group and females were found to predict utilitarian responses to personal moral dilemmas. When comparing percentage utilitarian responses there were no significant differences noted for the non-moral and impersonal moral dilemmas but the stressed group showed significantly less utilitarian responses compared to control subjects. The stress response was significantly negatively correlated with utilitarian responses. Females also showed significantly less utilitarian responses than males. We conclude that activation of the stress response predisposed participants to less utilitarian responses when faced with high conflict personal moral dilemmas and suggest that this offers further support for dual process theory of moral judgment. We also conclude that females tend to make less utilitarian personal moral decisions compared to males, providing further evidence that there are gender differences in moral reasoning.